Daya Tahan Hidup Pseudomonas putida Strain Pf-20 dalam Beberapa Macam Inokulum - Yenny Wuryandari; Triwidodo Arwiyanto; Bambang Hadisutrisno; I. Hartana (Jurnal Perlindungan Tanaman Indonesia, 2004)
For any crop-protection agent, an efficient formulation is a necessity to translate laboratory activity into adequate field performance. There are particular challenges to be faced in formulation of biological control agents, because the active ingredient is a living organism that must be kept relatively immobile and inactive while in storage, but quickly resume its  normal metabolic processes once applied to the target site. The objective of the research was  to study survival of Pseudomonas putida strain Pf-20 in various formulations at the storage  time and germination. The twelve formulations include carriers, additives and concentration  of Pf-20. The efficacy of various formulation in maintaining the population of Pf-20 in storage was assessed. The research result showed that population of Pf 20  in the formulation  number seven was the highest, with the combination peat+talc, CMC+arginin and  concentration of Pf[20 10^10 CFU/ml. In peat+talc, CMC+arginin, Pf-20 10^10  CFU/ml based formulation the bacteria survived even up to 84 days of storage although the population declined. In all formulations, population of Pf-20 increased at the time of seed germination. At the time of seed germination, formulation number seven was the highest too.